Environmental factors explain socioeconomic prevalence differences in myopia in 6-year-old children - Tideman, J Willem L; Polling, Jan Roelof; Hofman, Albert; Jaddoe, Vincent WV; Mackenbach, Johan P; Klaver, Caroline CW (British journal of ophthalmology, 2018)
PurposeHigh myopia (≤−6 D) usually has its onset before 10 years of age and can lead to blinding complications later in life. We examined whether differences in myopia prevalences in socioeconomic risk groups could be explained by differences in lifestyle factors.MethodsA total of 5711 six-year-old children participating in the prospective population-based birth cohort study Generation R underwent a stepwise ophthalmic examination, which included visual acuity and objective cycloplegic refraction to identify children with myopia (≤−0.5D). Daily activities, ethnicity, factors representing family socioeconomic status and housing were ascertained by questionnaire. Risk assessments of myopia and mediation analyses were performed using logistic regression; attenuation of risks was calculated by bootstrapping.ResultsPrevalence of myopia was 2.4% (n=137). Myopic children spent more time indoors and less outdoors than non-myopic children (p<0.01), had lower vitamin D (p=0.01), had a higher body mass index and participated less in sports (p=0.03). Children of non-European descent (OR 2.60; 95% CI 1.84 to 3.68), low maternal education (OR 2.27; 95% CI 1.57 to 3.28) and low family income (OR 2.62; 95% CI 1.8 to 3.74) were more often myopic. Lifestyle factors explained the majority of the increased risk for ethnicity (82%; 95% CI 55 to 120), maternal education (69%; 95% CI 45 to 109) and family socioeconomic status (71%; 95% CI 46 to 104).ConclusionThis study found environmental factors to be strong risk factors for myopia already at the age of 6 years. The myopia prevalence differences in socioeconomic groups were greatly determined by differences in distribution of these environmental risk factors, highlighting the importance of lifestyle adjustments in young children developing myopia.